Magneto-Biostratigraphy, Paleobathymetry, and Basin Subsidence History of Taiwan Coastal Range - Lai, Larry Syu-Heng; Dorsey, Rebecca J.; Horng, Chorng-Shern; Chi, Wen-Rong; Shea, Kai-Shuan; Yen, Jiun-Yee (figshare, 2022)
This repository is the supplementary dataset used for sedimentary basin analysis in the Taiwan's Coastal Range. The results are about to be published in a paper titled "Extremely rapid up-and-down motions of island arc crust during arc-continent collision" by Lai et al. at the journal Communications Earth & Environment. Four Microsoft Excel spreadsheets include sample information, data, and analytic results of rock paleomagnetism, calcareous nannoplankton biostratigraphy, planktonic foraminifera biostratigraphy, foraminifera-based paleobathymetry estimates, and basin subsidence analysis.The R scripts developed for these analyses are stored in another Zenodo repository: https://doi.org/10.5281/zenodo.5823613Citation: If you consider using these scripts and data, please cite the following references:Lai, L.S.-H., Dorsey, R.J., Horng, C.-S., Chi, W.-R., Shea, K.-S., and Yen, J.-Y. (Accepted) Extremely rapid up-and-down motions of island arc crust during arc-continent collision. Communications Earth & Environment .Lai, L.S.-H., Dorsey, R.J., Horng, C.-S., Chi, W.-R., Shea, K.-S., and Yen, J.-Y. (2021) Polygenetic mélange in retrowedge foredeep of an active arc-continent collision, Coastal Range of eastern Taiwan. Sedimentary Geology , v. 418, 105901. https://doi.org/10.1016/j.sedgeo.2021.105901